Strategi Pedagogis Pendidikan Kristen dalam Menjawab Fenomena Deconstruction of Faith pada Generasi Muda - Yonggi Sampelan (Sekolah Tinggi Agama Kristen Diaspora Wamena, 2026)
The phenomenon of deconstruction of faith among young people has emerged as a significant challenge for Christian Education in the digital era. Rather than representing a decline in faith, it often reflects a critical process through which individuals reconstruct a more personal and meaningful understanding of their beliefs. This study aims to analyze the phenomenon of deconstruction of faith and formulate a pedagogical strategy for Christian Education that effectively responds to this challenge. A qualitative library research approach was employed by examining scholarly journal articles, academic books, and relevant literature on Christian Education, faith development, transformative learning, and deconstruction of faith. The data were analyzed using content analysis through identification, categorization, synthesis, and interpretation of major themes. The findings indicate that deconstruction of faith should be understood as part of faith development rather than religious decline. The phenomenon is influenced by identity formation, digital culture, and the increasing capacity of young people for critical reflection. Based on the synthesis of the literature, this study proposes an Integrative Pedagogical Strategy for Christian Education that combines Stages of Faith Development, Transformative Learning Theory, and Cultural Liturgies as a conceptual framework for accompanying young people's faith reconstruction. The proposed strategy emphasizes dialogical learning, critical reflection, faith development mentoring, spiritual formation, and contextual learning communities as essential elements of contemporary Christian Education Abstrak Fenomena deconstruction of faith pada generasi muda menjadi salah satu tantangan penting bagi Pendidikan Kristen di era digital. Proses ini tidak selalu menunjukkan kemerosotan iman, tetapi sering kali merupakan refleksi kritis yang mendorong individu membangun kembali keyakinannya secara lebih personal dan bermakna. Penelitian ini bertujuan menganalisis fenomena deconstruction of faith serta merumuskan strategi pedagogis Pendidikan Kristen yang relevan dalam mendampingi generasi muda. Penelitian menggunakan pendekatan kualitatif melalui metode penelitian kepustakaan (library research) dengan menganalisis berbagai artikel ilmiah, buku akademik, dan literatur yang berkaitan dengan Pendidikan Kristen, perkembangan iman, pembelajaran transformatif, dan deconstruction of faith. Data dianalisis menggunakan teknik content analysis melalui proses identifikasi, kategorisasi, sintesis, dan interpretasi tema-tema utama. Hasil penelitian menunjukkan bahwa deconstruction of faith lebih tepat dipahami sebagai bagian dari perkembangan iman daripada sebagai bentuk kemerosotan religiusitas. Fenomena ini dipengaruhi oleh perkembangan identitas, budaya digital, serta meningkatnya kemampuan refleksi kritis generasi muda. Berdasarkan sintesis temuan, penelitian ini menghasilkan Strategi Pedagogis Integratif Pendidikan Kristen yang mengintegrasikan Stages of Faith Development, Transformative Learning Theory, dan Cultural Liturgies sebagai kerangka konseptual dalam mendampingi proses rekonstruksi iman generasi muda. Strategi tersebut menekankan pentingnya pembelajaran dialogis, refleksi kritis, pendampingan perkembangan iman, praktik spiritual, serta pembentukan komunitas belajar yang kontekstual dan transformatif